UNITARY ARCHITECTURE IN THE NIGERIAN FEDERAL STRUCTURE: ASSESSMENT AND IMPLICATIONS ON GOVERNANCE - Fatai Adesanmi , Olubunmi; Ajayi, Olufemi (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
This paper examined the unitary architecture in the operation of the Nigerian federalism, with a view to showing a clear departure from the tenets of the system. The way the Nigeria’s federalism is operated makes the system defective. Federalism favours decentralisation of power and resources among the units, but unfortunately the practice since the advent of 1966 coup in Nigeria has been skewed towards unitary system as more and more powers and resources are being allocated to the central government. This paper aimed at highlighting the areas and establishes the impacts of the over-centralisation of power, a major attribute of unitary system of government in the Nigeria federal arrangement and to bring out its implications on the federating units. In the 1999 Constitution, 68 items are contained in the exclusive list while 30 items were contained in the concurrent list and the residual list so meagre as reflected in the fourth schedule of the 1999 constitution, a clear departure from the independence constitution. The study relied heavily on secondary data, and adopted content analysis was adopted for the analysis of the information generated. The study found evidence of unitary arrangement in the operation of the Nigerian federalism i.e.: the increase in the exclusive lists which further deplete the concurrent lists, whittling down the powers of the federating units on resource control, arrangement of police, the court system among others, which negates the principles of federalism. To get out of the political, economic and social morass being experienced in Nigeria, the paper recommended that the country re-federalize its governance.